2017
DOI: 10.1088/1742-6596/849/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

High-dynamic-range water window ptychography

Abstract: Ptychographic imaging with soft X-rays, especially in the water window energy range, suffers from limited detector dynamic range that directly influences the maximum spatial resolution achievable. High-dynamic-range data can be obtained by multiple exposures. By this approach we have increased the dynamic range of a ptychographic data set by a factor of 76 and obtained diffraction signal till the corners of the detector. The real space half period resolution was improved from 50 nm for the single exposure data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…5(a)]. In accordance with literature, only the central lobe has been fitted with a Gaussian in order to determine the transverse coherence length [12,47,50]. It has been suggested that the increase of the CCF at larger ∆r arises from the contribution of higher residual coherence modes to the fundamental coherent mode [51].…”
Section: Spatial-coherence Measurements At the Beamline P04 At Petra IIImentioning
confidence: 78%
See 1 more Smart Citation
“…5(a)]. In accordance with literature, only the central lobe has been fitted with a Gaussian in order to determine the transverse coherence length [12,47,50]. It has been suggested that the increase of the CCF at larger ∆r arises from the contribution of higher residual coherence modes to the fundamental coherent mode [51].…”
Section: Spatial-coherence Measurements At the Beamline P04 At Petra IIImentioning
confidence: 78%
“…To gain detailed knowledge of the coherence properties of X-ray radiation, its manipulation, and especially its preservation plays an increasingly important role at synchrotron beamlines, not least because of present and future upgrades of synchrotron facilities to diffraction-limited storage rings, e.g., PETRA IV [1], ALS-U [2,3], ESRF-EBS [4] or MAX IV [5]. The most obvious beneficiaries of a high coherent flux are coherent imaging and scattering experiments such as Fourier-transform holography (FTH) [6][7][8][9], X-ray ptychography [10][11][12][13], coherent diffractive imaging (CDI) [14][15][16], scanning transmission X-ray microscopy (STXM) [17][18][19], as well as X-ray photon correlation spectroscopy (XPCS) [20][21][22]. For these experiments, the knowledge of the intrinsic coherence properties of the X-ray source, as well as the impact of beamline apertures and optics, is essential for optimizing the experimental conditions and a correct interpretation of the data.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical element specific contrast was also obtained in another study to highlight the unique imaging opportunities in the water window [25]. We have tested high-dynamic range (HDR) ptychographic measurements using double exposures with and without beam stop on a test sample and achieved 18 nm resolution [26]. In this work we present the significant improvement of (HDR) measurements of a biological cell with soft X-rays using double exposures with and without beam stop.…”
Section: Introductionmentioning
confidence: 94%